Graphical Analysis of the Growth Rate of National Economies by Considering the Supply Chain Strategy in 25 Countries over the Period From 2000 to 2016 - V.V. Ponkratov; A.K. Karaev; S.N. Silvestrov; N.V. Kuznetsov; D.A. Smirnov; N.E. Kotova (International Journal of Supply Chain Management, 2019)
The article presents the graphical analysis of economic indicators for 25 countries: GDP growth rate (%) and GDP per person employed (thousand US dollars) for the period from 1990 to 2016 by considering the supply chain strategy (SCS) and transparency. The authors carried out the decomposition of economic growth rates of selected countries according to the following factors: 1) extensive factors – the growth rate of the capital stock and the size of labor force; 2) intensive factors – RD expenditures; 3) the dynamics of foreign direct investment in the country 4) supply chain strategy. Over the past 16 years, only a few countries from the sample have shown growth of the national economy higher than the growth rates of the world economy. These are China, Turkmenistan, India, Malaysia, and Singapore (their economies grew at a rate of more than 5% per year). The most dynamic renewal of fixed assets can be observed in China, the United States and Japan. At the same time, over the past 10 years China has demonstrated an active investment policy, increasing the investment in fixed assets almost five times. China and India were countries that most actively used the size of labor force as a factor of extensive growth. Korea, Japan, Germany, USA, China and Singapore demonstrated the most dynamic growth in RD expenditures. Despite the non-monotonous dynamics of foreign direct investment in these countries, over the entire period of observation from 1990 to 2017, the United States has been the most attractive country for foreign direct investment. At the same time, the most significant growth in foreign direct investment was recorded in China and, recently, in the United Kingdom.